Inflation and financial development: evidence from Brazil - Manoel Bittencourt (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2007)
We examine the impact of inflation on financial development in Brazil and the data available permit us to cover the period between 1985 and 2002. The resultsbased initially on time-series and then on panel time-series data and analysis, and robust for different estimators and financial development measuressuggest that inflation presented deleterious effects on financial development at the time. The main implication of the results is that poor macroeconomic performance, exemplified in Brazil by high rates of inflation, have detrimental effects to financial development, a variable that is important for affecting, e.g. economic growth and income inequality. Therefore, low and stable inflation, and all that it encompasses, is a necessary first step to achieve a deeper and more active financial sector with all its attached benefits.
Keywords: E31; E44; O11; O54; 330; Inflation; Finanzsektor; Entwicklung; Brasilien